Openness Management by Figures as a Model of Integrity and Transparency - Al-anizi, Sa’ad; Isma'eel, Mustafa muneer (Journal of Economics and Administrative Sciences, 2010)
Competitive advantage is a substantial  strategic objective for organizations. It requires high levels in the quality of products and services provided to customers, continuous improvement of costing , care for creativity and innovative employees, and speed unique to the marketing and financial engineering, and business re-engineering processes. The situation in this area, requires actors to attract and develop human resources, including help in proper implementation of the strategic tasks that targeted by those institutions. According to the opinions and viewpoints of management scholars, the competitive advantage resource is the most important issue for organizations in the third millennium, which can be achieved through the construction of organizational knowledge, human capital, and their development to serve in transforming them into the learning and expert organizations, to know how to accelerate to be more efficient and flexible in the market.